Training and Learning Need Analysis Based on Soft and Hard Competences Gap (Case Study in PT. Bank X) - Sujarwadi, Edy Tri; Tjakraatmadja, Jann Hidajat (The Indonesian Journal of Business Administration, 2012)
The study aim to analyze employee competency gaps at the branch level and then develop them through training and learning process. The analysis covers the soft and hard competence.Â  The soft competence includes achievement motivation, communication skills, problem solving, teamwork, integrity, accountability and respect to others. The hard competence include marketing management/product selling, risk management, operational management, systematicallyÂ  thinking-cross function, product knowledge, product selling approval process, and working procedure related to his/her job, understanding financial statement of company / business unit and company vision, mission and strategy. To conduct mapping of competence gap it is used competency model through clearly defining for each competency level. The results of the gap analysis will be an input to run training and learning, based on the level of employee competence gaps. In order to implement the study, it is prepared a Training Program Outline (TPO) for each required competencies. Keywords: sharia banking, human resources (HR), competency gaps, training and learning